2015
DOI: 10.1371/journal.pone.0136446
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Relaxing Music on Mental Fatigue Induced by a Continuous Performance Task: Behavioral and ERPs Evidence

Abstract: The purpose of this study was to investigate whether listening to relaxing music would help reduce mental fatigue and to maintain performance after a continuous performance task. The experiment involved two fatigue evaluation phases carried out before and after a fatigue inducing phase. A 1-hour AX-continuous performance test was used to induce mental fatigue in the fatigue-inducing phase, and participants’ subjective evaluation on the mental fatigue, as well as their neurobehavioral performance in a Go/NoGo t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 35 publications
3
24
0
1
Order By: Relevance
“…The decreased NoGo-P3 amplitude suggested that participants experienced increased difficulty in allocating cognitive resources to NoGo stimuli. These changes in the Go-P3 and NoGo-P3 amplitude were consistent with the results of Kato et al [ 14 ] but were inconsistent with Guo et al [ 15 ]. The inconsistency between the results of Guo et al and our results may be caused by different settings of stimulus ratios.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The decreased NoGo-P3 amplitude suggested that participants experienced increased difficulty in allocating cognitive resources to NoGo stimuli. These changes in the Go-P3 and NoGo-P3 amplitude were consistent with the results of Kato et al [ 14 ] but were inconsistent with Guo et al [ 15 ]. The inconsistency between the results of Guo et al and our results may be caused by different settings of stimulus ratios.…”
Section: Discussionsupporting
confidence: 72%
“…The induction of mental fatigue and the assessment of response inhibition in the previous studies [ 13 15 ] were investigated based on traditional psychological cognitive tasks, e.g., a continuous Go/NoGo task. However, the fatigue level and operation performance are modulated by the characteristics of tasks performed [ 34 ]; therefore, mental fatigue induced by cognitive tasks in the laboratory environment made their conclusions difficult to apply to real-life situations.…”
Section: Discussionmentioning
confidence: 99%
“…Arikan et al reported that listening to well-known music promotes attention and increases the P300 amplitude of ERPs 22. Moreover, Guo et al showed that, by listening to music that can cause subjective relaxation, there is a decrease in the performance deficit resulting from mental fatigue during work that applies cognitive exercise and an increase in the P300 amplitude in ERPs 23. Although these studies have indicated the definite result that the cognitive exercise function is promoted by listening to music that is well-known or is relaxing, there has been no discussion on whether increased ERP amplitude results from a direct physical effect of music, or whether it is a secondary effect of changes in subjective mental activity (eg, comfort).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that one of the meanings and senses of music demonstrates that mentally fatigued individuals, when coming into contact with music and its expressions, experience a reduction of their mental exhaustion and of the psychomotor deterioration, both at the behavioral and cognitive levels (20) .…”
Section: Discussionmentioning
confidence: 99%